2020
DOI: 10.1111/opo.12747
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of vergence/accommodative therapy for accommodative dysfunction in children with convergence insufficiency

Abstract: Purpose To determine the effectiveness of office‐based vergence/accommodative therapy for improving accommodative amplitude and accommodative facility in children with symptomatic convergence insufficiency and accommodative dysfunction. Methods We report changes in accommodative function following therapy among participants in the Convergence Insufficiency Treatment Trial – Attention and Reading Trial with decreased accommodative amplitude (115 participants in vergence/accommodative therapy; 65 in placebo ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…noted (Chen et al, 2021). F(+) means that the subjects had more difficulty in +2.00 D, whereas F(−) means that they experienced more difficulty in −2.00 D.…”
Section: Accommodative Facility Testmentioning
confidence: 99%
“…noted (Chen et al, 2021). F(+) means that the subjects had more difficulty in +2.00 D, whereas F(−) means that they experienced more difficulty in −2.00 D.…”
Section: Accommodative Facility Testmentioning
confidence: 99%
“…Consistent with prior studies of symptoms in accommodative and convergence insufficiency, decreased amplitude of accommodation was defined as monocular amplitude of accommodation more than 2D below the minimum expected amplitude based on the participant's age (15 – ¼ age) 6,24,26,37,38 . Decreased accommodative facility was defined as <6 cycles per minute, which is 1 SD below the normative value of 11 cpm for school‐age children 6,7,39,40 …”
Section: Methodsmentioning
confidence: 95%
“…Mutual interactions between vergence and accommodation are well known, 1,2 and it is commonly accepted that patients often have concurrent dysfunction in both systems 3‐9 . Clinically, convergence insufficiency (CI) and accommodative dysfunction are associated with symptoms that occur when reading or performing other near work, such as blurred vision, headaches, asthenopia, frequent loss of place or poor concentration 3,4,10–23 …”
Section: Introductionmentioning
confidence: 99%
“…The Convergence Insu ciency Treatment Trial (CITT) study group [14,15] reported that o ce-based vergence/accommodative therapy (OBVAT) was more effective than home-based push-up therapy, computer-based vision therapy, and o ce-based placebo therapy for improving binocular function in patients with convergence insu ciency. Other studies [16,17] also showed that OBVAT produced signi cant improvements in monocular accommodative amplitude and facility. Some studies [18,19] that investigated the effects of OBVAT on attention and reading in children with convergence insu ciency found that it could improve reading comprehension, reading speed, and academic behavior.…”
Section: Introductionmentioning
confidence: 75%